The number of nephrons in different glomerular diseases - Viggiano,Davide; Nigro,Michelangelo; Sessa,Francesco; Vignolini,Graziano; Campi,Riccardo; Serni,Sergio; Pollastro,Rosa Maria; Vallone,Gianfranco; Gigliotti,Giuseppe; Capasso,Giovambattista (PeerJ, 2019)
Background The total number of nephrons has been measured mainly from post-mortem studies and only in selected populations. Data from living subjects are scanty, and direct comparisons among different glomerular diseases are lacking. The present work exploits modern methodology to estimate the total nephron number in glomerulopathies with prevalent proteinuria/nephrotic syndrome versus glomerulopathies with nephritic syndrome (IgA nephropathy (IgAN), lupus nephritis), thus extending previous observations about the number and function of glomeruli in different physiological and pathological states. Methods This is a retrospective study based on one hundred and seven patients who have undergone renal biopsy. The glomerular density has been estimated from the biopsy specimens and the total cortical volume has been obtained from ultrasound recordings. Stereological methods have been applied to calculate the total number of nephrons and their volume. The correlation between clinical parameters and quantitative morphological data have studied using the Pearson correlation coefficient (r). Results The total number of nephrons inversely correlated with the systolic blood pressure (r = −0.4, p < 0.05). In proteinuric diseases, such as focal segmental glomerulo-sclerosis (FSGS), membranous nephropathy (MN) and diabetes, the change in estimated GFR (eGFR) directly correlated with the total number of non-sclerotic glomeruli (NSG) (r = 0.62, p < 0.01), whereas in nephritic syndrome no significant correlation was observed. The alterations in eGFR occurring in nephritic syndromes such as IgAN cannot be explained on the basis of the number of NSG. Discussion The fusion of the podocyte foot-processes that typically occurs in purely proteinuric diseases does not modify the glomerular filtration rate: therefore in these situations, the change in eGFR depends mainly on the number of available glomeruli. On the other side, the eGFR decrease occurring in nephritic syndromes, such as IgAN, cannot be explained simply on the basis of the number of NSG and likely depends on the substantial involvement of the mesangial axis. Future studies should verify whether these changes are reversible with appropriate therapy, thus reversing eGFR decrease.
Keywords: Nephron number; eGFR; Blood pressure; Nephrotic syndrome; Nephritic syndrome; IgA nephropathy; Diabetic nephropathy; Membranous nephropathy; Minimal change disease; Podocytes